Two-dimensional stable and ultrathin cluster-based metal–organic layers for efficient electrocatalytic water oxidation. Issue 26 (21st June 2021) - Yu, Bin-Bin; Hua, Yi-Wei; Huang, Qi; Ye, Si-Yuan; Zhang, Hao-Dong; Yan, Zheng; Li, Rui-Wen; Wu, Jun; Meng, Yan; Cao, Xuebo
Abstract : The report describes the successful synthesis of CoNi bimetal two-dimensional CMOLs directly grown on Ni foam (Co 0.6 Ni 0.4 -CMOLs/NF ), which shows excellent catalytic activity and stability for the OER under alkaline conditions. Abstract : For electrochemical energy conversion, highly efficient and stable electrocatalysts are required, which are principally designed and synthesized by virtue of structural regulation. Two-dimensional cluster-based metal–organic layers (CMOLs) would have good performance in oxygen evolution reaction (OER) because of their stable and layered structure. Here, we first report the synthesis of CoNi bimetal two-dimensional CMOLs directly grown on Ni foam, which show excellent catalytic activity for the OER under alkaline conditions. Co 0.6 Ni 0.4 -CMOLs exhibited the best OER performance, compared with Co-CMOLs and Ni-CMOLs . The findings are expected to help understand the fundamental concept of enhanced electrochemical activity based on pristine metal–organic frameworks with high stability.